Characteristics of fluid dynamics in tubes and the outflow tract of an artificial heart, measured with pulsed US Doppler technique - POHL, M.; WENDT, M. O.; PARDEMANN, G.; LERCHE, D. (Archives of Acoustics, 1984)
Velocity profiles and turbulence intensities of steady flow in tubes were measured with a pulsed ultrasonic-Doppler instrument IMP 30. These results were compared with those of other flow measurement methods. In a similar way such measurements were performed to study pulsatile flow in the inflow- and the outflow-tract of an artificial heart, developed by the Hospital of Internal Medicine, Wilhelm-Pieck-University, Rostock. The principles of signal acquisition and first results are presented.